Diversity of endophytic fungi isolated from different plant parts of Acacia mangium, and antagonistic activity against Ceratocystis fimbriata, a causal agent of Ceratocystis wilt disease of A. mangium in Malaysia - Ahmad, Mohd Farid; Zahari, Rozihawati; Mohtar, Mastura; Wan-Muhammad-Azrul, Wan Azhar; Hishamuddin, Muhammad Syahmi; Samsudin, Nik Iskandar Putra; Hassan, Affendy; Terhem, Razak (Frontiers Media, 2022)
Acacia mangium is an important wood for commercial products especially pulp and medium-density fibreboard. However, it is susceptible to Ceratocystis fimbriata infection, leading to Ceratocystis wilt. Therefore, the present work aimed to (i) establish the diversity of endophytic fungi in different plant parts of A. mangium,and (ii) evaluate the antifungal potentials of the isolated and identified endophytic fungi against C. fimbriata. Endophytic fungal identification was conducted by PCR amplification and sequencing of the internal transcribed spacer 1 (ITS1) and ITS4 regions of nuclear ribosomal DNA. A total of 66 endophytic fungi were successfully isolated from different parts of A. mangium; leaf (21), stem (13), petiole (12), root (9), flower (6), and fruit (5). The endophytic fungal isolates belonged to Ascomycota (95.5%) and Zygomycota (4.5%). For Ascomycota 13 genera were identified: Trichoderma (28.6%), Nigrospora (28.6%), Pestalotiopsis (12.7%), Lasiodiplodia (9.5%), Aspergillus (6.3%), Sordariomycetes (3%), and Neopestalotiopsis, Pseudopestalotiopsis, Eutiarosporella, Curvularia, Fusarium, Penicillium, and Hypoxylon each with a single isolate. For Zygomycota, only Blakeslea sp. (5%) was isolated. Against C. fimbriata, Trichoderma koningiopsis (AC 1S) from stem, Nigrospora oryzae (AC 7L) from leaf, Nigrospora sphaerica (AC 3F) from the flower, Lasiodiplodia sp. (AC 2 U) from fruit, Nigrospora sphaerica (AC 4P) from petiole, and Trichoderma sp. (AC 9R) from root exhibited strong inhibition for C. fimbriata between 58.33 to 69.23%. Thus, it can be concluded that certain endophytic fungi of A. mangium have the potential to be harnessed as anti-Ceratocystis agent in future biotechnological applications.